Fungsi Petugas Keamanan dalam Meningkatkan Pendapatan Masyarakat Nelayan di Kabupaten Kepulauan Talaud - Pandaleke, Alfien (Universitas Brawijaya, Indonesia, 2014)
Purpose of research is to know how function of security guard in increasing earnings of msyarakat fisherman in Kabupaten Kepulauan Talaud. Population is all fisherman public and sample is 75 respondents. Based on result of research by using product correlation analysis moment with hypothesis expressing there is function of security guard in increasing earnings of fisherman public in Kabupaten Kepulauan Talaud. Means hypothesis received to know level of determination energy power function of security guard in increasing earnings of fisherman in Kabupaten Kepulauan Talaud hence result of his is 62% means earnings of fisherman public in Kepulauan Talaud 62% influenced by management of human resource, same job, and service of public and 48% determined by other factor of which is not checked by researcher. By need to increase same job of security guard and service of fisherman public causing can obey orders which have been specified to be able to increase its the earnings.